Formation of physical qualities in young basketball players - Sablin A.B.; Kornishin I.I.; Ulyanova E.A.; Khvostenko S.Yu. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to increase the physical fitness of basketball players aged 13-14 years at the initial stage of the general education training cycle. Methods and structure of the study. The research involved 40 basketball players from the Dynamo Sports School in Moscow, who trained four times a week for 90 minutes. The pedagogical experiment, designed for the period from September 3 to December 3, 2024, included an assessment of physical qualities according to the following criteria: 30-meter run, 3x10-meter shuttle run, long jump, pull-ups, 6-minute distance run and forward tilt. Results and conclusions. In the control group, after completion of the experiment, an increase in all tests was observed by 4-7%, but only in the 6-minute running test the increase reached a statistically significant level (1126±16 to 1182±14, p<0.05). The experimental group showed more significant progress, with an average increase in the range of 8-16% over the entire study period. Although the indicators in the forward bending and crossbar pull-up test increased (from 6.1±0.8 to 6.8±0.6 and from 9.1±1.8 to 9.8±1.5, respectively), no statistically significant differences could be identified (p>0.05). If you perform a set of physical exercises aimed at developing physical qualities during basketball training sessions at the general preparatory stage of training with athletes aged 13-14, their performance will significantly improve. The solution of the hypothesis is confirmed by the results of scientific research.